Caracterização de acessos de bananeira - Mattos, Lorenna Alves Mattos (2009)
The banana genetic breeding program, initiated at Embrapa Cassava and Tropical Fruits in 1983, is mainly focused on the improvement of diploids and further crosses of these diploids with AAB Prata and Silk type triploids, generating AAAB tetraploids. The main objective is to develop varieties resistant to pests and nematodes that are productive, with reduced height and crop cycle, maintaining the Prata and Silk fruit flavors. Throughout it´s 26 years, the banana genetic breeding program has recommended the following cultivars: Caipira, Thap Maeo, FHIA 18, Prata Graúda, Prata Baby (Nam), Pacovan Ken, Japira, Vitória, Preciosa, Tropical, Maravilha, Caprichosa, Garantida and Princesa. The characterization and evaluation of banana genotypes, by selecting the main productive and most resistant to pests, are the main steps to the genetic breeding program, and constitutes a significant solution for increases in yield and fruit quality. In order for a breeding program to be successful, there has to be enough genetic variability regarding the traits of interest. Therefore, agronomical as well as the fruit physical and chemical characteristics associated to the use of modern molecular tools, provides useful information for plant breeders. This work was carried out at the experimental field, Plant Physiology Laboratory and Molecular Biology Laboratory of the Embrapa Cassava and Tropical Fruits, aiming to characterize 26 banana accessions regarding 12 agronomical, 14 fruit physical and chemical characteristics and using 13 SSR markers. This work was subdivided into three chapters: the objective of the first chapter was to characterize the accessions regarding their agronomical and fruit physical and chemical characteristics; the second one was to try to associate the fruit physical and chemical characterization with SSR markers and the third one combined agronomical and fruit physical and chemical characteristics and molecular data in order to obtain genetic diversity information between the accessions using the Gower algorithm. The results suggest a broad genetic variability for all the agronomic and fruti physical and chemical characteristics among the 26 banana accessions. Furthermore, the SSR markers were efficient in quantifying the genetic variability available between these accessions. The Gower algorithm combined the agronomic and molecular data being a powerful tool for the quantification of banana genetic variability.